Developmental changes in orienting towards faces: A behavioral and eye-tracking study. (March 2020) - Hirai, Masahiro; Muramatsu, Yukako; Nakamura, Miho
Previous studies show that newborn infants and adults orient their attention preferentially toward human faces. However, the developmental changes of visual attention captured by face stimuli remain unclear, especially when an explicit top-down process is involved. We capitalized on a visual search paradigm to assess how the relative strength of visual attention captured by a non-target face stimulus and explicit attentional control on a target stimulus evolve as search progresses and how this process changes during development. Ninety children aged 5–14 years searched for a target within an array of distractors, which occasionally contained an upright face. To assess the precise picture of developmental changes, we measured: (1) manual responses, such as reaction time and accuracy; and (2) eye movements such as the location of the first fixation, which reflect the attentional profile at the initial stage, and looking times, which reflect the attentional profile at the later period of searching. Both reaction time and accuracy were affected by the presence of the target-unrelated face, though the interference effect was observed consistently across ages. However, developmental changes were captured by the first fixation proportion, suggesting that initial attention was preferentially directed towards the target-unrelated face before 6.9 years of age. Furthermore, prior to 12.8 years of age, the first fixation towards face stimuli was significantly more frequent than for object stimuli. In contrast, the looking time proportion for the face stimuli was significantly higher than that for the objects across all ages. These findings suggest that developmental changes do not influence the later search periods during a trial, but that they influence the initial orienting indexed by the first fixation. Moreover, the manual responses are tightly linked to eye movement behaviors.